Gelar Profesor Kehormatan: Kutub Capaian Prestasi dan Marwah Akademik - Siti Lailiyah; Robingun Suyud El Syam; Muhammad Saefullah; Ashief El Qorny; Luluk Alawiyah (Departement of Mathematics Education, 2023)
The research aims to examine the title of honorary professor from the poles of academic achievement and marwah, emphasizing solutions from different perceptions. The article is a qualitative research with a phenomenological approach. The research concluded that Honorary Professor is an academic title of professor from a tertiary institution which is awarded as a form of appreciation to everyone from non-academic circles for having extraordinary achievements. The title of professor through the academic route must be obtained with difficulty, while for non-academic it is feared that it will be used for political-economic interests which can open transactional loopholes. The academic community must encourage the awarding of honorary degrees to run transparently and on target so that negative potential can be avoided.